2012
DOI: 10.1155/2012/369751
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Associated with Infections of the Jaws

Abstract: The microbial infections involving the craniofacial skeleton, particularly maxilla and mandible, have direct relationship with the dental biofilm, with predominance of obligate anaerobes. In some patients, these infections may spread to bone marrow or facial soft tissues, producing severe and life-threatening septic conditions. In such cases, local treatment associated with systemic antimicrobials should be used in order to eradicate the sources of contamination. This paper discuss the possibility of spread of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 91 publications
(131 reference statements)
0
15
0
2
Order By: Relevance
“…Isolation of DNA from the surgical bone specimen or detection of E. coli and Enterococcus genes associated with specific virulence factors by polymerase chain reaction analysis may have been more effective in confirming whether those pathogens had been inoculated into the bone through the existing extraction wound. We speculate that the density (bacterial load) and/or virulence of enterococci, the ecological associations and/or interactions within the whole bacterial community present in the site of the bone infection, and other host‐related factors such as a possible temporary disturbance of the local immune defence may have been involved in the pathogenesis of this particular case. While it would have been ideal to investigate the immunocompetence of the patient by laboratory tests, this was not possible in our case; however, a thorough medical history did not reveal any suggestion of diabetes mellitus, HIV infection or other immunosuppression conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Isolation of DNA from the surgical bone specimen or detection of E. coli and Enterococcus genes associated with specific virulence factors by polymerase chain reaction analysis may have been more effective in confirming whether those pathogens had been inoculated into the bone through the existing extraction wound. We speculate that the density (bacterial load) and/or virulence of enterococci, the ecological associations and/or interactions within the whole bacterial community present in the site of the bone infection, and other host‐related factors such as a possible temporary disturbance of the local immune defence may have been involved in the pathogenesis of this particular case. While it would have been ideal to investigate the immunocompetence of the patient by laboratory tests, this was not possible in our case; however, a thorough medical history did not reveal any suggestion of diabetes mellitus, HIV infection or other immunosuppression conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, the probability of haematogenous spread cannot totally be excluded, though it is considered uncommon in jaw osteomyelitis. Bacteraemia, though with a low rate of Enterococcus involvement, has been found in 57.9% of post‐extraction cases, whereas Gaetti‐Jardim et al . suggested that the dissemination of oxygen‐tolerant micro‐organisms, such as enteric rods, is likely to take place during haematogenous spread.…”
Section: Discussionmentioning
confidence: 99%
“…The most relevant infections are lateral and apical periodontitis, osteomyelitis, peri-implantitis, and their complications, such as facial cellulitis and other infections involving deep spaces of face and neck [135]. Microbiota associated with infections of the craniofacial skeleton, particularly maxilla and mandible, are polymicrobial in nature and a mix of aerobic-anaerobic genera.…”
Section: Infections Associated To Craniofacial Skeletonmentioning
confidence: 99%
“…Anaerobic bacteria are predominant in the oral microflora of humans and several animal species, highlighting the anaerobic Gram-negative producers of black pigment, which belong to the Porphyromonas and Prevotella genera, and were identified in cases of chronic periodontitis, biofilm associated gingivitis and osteomyelitis in humans (Ashimoto et al 1996, Socransky et al 1998, Mayanagi et al 2004, Gaetti-Jardim Jr et al 2010. In pet animals, these microorganisms were also identified in the oral microflora of cats with or without periodontal disease (Mallonee et al 1988, Love et al 1989, Love et al 1990) as well as in periodontal pockets of dogs (Hardham et al 2005, Nishiyama et al 2007, Riggio et al 2011, Senhorinho et al 2011).…”
Section: Introductionmentioning
confidence: 99%